Propuesta para la creación de una microempresa comercializadora de tintes textiles biodegradables en Otavalo - Haro, Carlos A. (2018)
The present titration work consists of a proposal for the creation of a microenterprise selling biodegradable textile dyes in the city of Otavalo, with the purpose of avoiding the habitual use of anilines and industrialized pigments that are corrosive to health and the environment. This proposal aims to give an economic option to those who use materials for textile dyeing, fostered in the city the offer of organic textile dyes for the dyeing of natural and synthetic fibers. The proposal is based on the theory of Adam Smith, whose approach is to promote free economy with the freedom of business, starting as an essential foundation, new business ventures in the market and with the ability to meet the expectations of society it requires it.